PERSEPSI MASYARAKAT TENTANG PATTIMURA PARK SEBAGAI RUANG TERBUKA HIJAU - Alexander Padatu; Gun Mardiatmoko; Ch. C. V. Suhendy (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
Understanding or perceptions of the Ambon city community about the existence of Pattimura Park as a public green open space and its benefits are important to dense population of people can perform various activities, recreation and interact actively. This study aims to determine the community perception of the Pattimura Park as a Public green open space. Research method used was accidental sampling method. The analysis, while the community perception using Chi-square analysis. The results showed that the knowledge of Pattimura Park = 84%, the attitudes = 81.33%, the opinions = 84% and the expectation that benefited = 74.67%. Their various activities in the Pattimura Park cause various perceptions of the park.